Reactions of cotton CNPA-ITA 90 to mepiquat chloride - Lamas, Fernando Mendes; Athayde, Manoel Luiz Ferreira; Banzatto, David Ariovaldo (Pesquisa Agropecuaria Brasileira, 2000)
The effects of different doses of mepiquat chloride on cotton (Gossypium hirsutum L.) plants, cultivar CNPA-ITA 90, during the 1993/94 and 1994/95 growing seasons were evaluated at Itamarati farm, Ponta Porã, MS, Brazil. The doses were split in three application dates and the experimental design was in randomized blocks, with five treatments replicated four times. The treatments were as follows: 1) unsprayed control; 2) 12.5+12.5+25.0 (50.0); 3) 25.0+25.0+25.0 (75.0); 4) 0.0+50.0+50.0 (100.0); and 5) 12.5+62.5+50.0 (125.0) g ha-1 of mepiquat chloride. The spraying was done at 34, 47 and 62 days after emergence (DAE) in 1993/94 and at 42, 60 and 73 DAE in 1994/95, when the plants were at the average hight of 51, 84 and 93 cm and 61, 79 and 97 cm, respectively. Increasing dose of mepiquat chloride caused decreasing in plant height; leaf stems and total above ground dry matter; number of nodes and branching; the branches length; the number of damaged fruits; the total number of bolls and the number of fully opened bolls.